Cohort Profile: Childhood morbidity and potential non-specific effects of the childhood vaccination programmes in the Nordic countries (NONSEnse): register-based cohort of children born 1990–2017/2018. Issue 2 (10th February 2023) - Gehrt, Lise; Laake, Ida; Englund, Hélène; Nieminen, Heta; Feiring, Berit; Lahdenkari, Mika; Palmu, Arto A; Trogstad, Lill; Benn, Christine Stabell; Sørup, Signe
Abstract : Purpose: The aim of the NONSEnse project is to investigate the non-specific effects of vaccines and immunisation programmes on the overall health of children by using information from the extensive nationwide registers on health and sociodemographic factors in Denmark, Finland, Norway and Sweden. Participants: The cohort covers 9 072 420 children aged 0–17 years, born 1990–2017/2018 and living in Denmark, Finland, Norway or Sweden. All countries use a unique identification number for its permanent residents, which makes it possible to link individual-level information from different registers. Findings to date: Data collection and harmonisation according to a common data model was completed in March 2022. As a prerequisite for comparing the effects of childhood vaccinations on the overall health of children across the Nordic countries, we have identified indicators measuring similar levels of infectious disease morbidity across these settings. So far, studies pertaining to non-specific effects of vaccines are limited to investigations that could be undertaken using aggregated data sets that were available before the NONSEnse cohort with individual-level information was completely set up. Future plans: We are currently performing several studies of the effects on non-targeted infectious disease morbidity across the countries following vaccination against measles, mumps, rubella, diphtheria, tetanus, pertussis, human papillomavirus, rotavirus and influenza. Multiple studies are planned within the next years using different study designs to facilitate triangulation of results and enhance causal inference. Registration: No clinical trials will be conducted within the NONSEnse project.